Proposed Improvement of Trans Semanggi Suroboyo Services Using IPA and QFD Methods - Setyani, Kartika; Ciptomulyono, Udisubakti (Hasanuddin Economics and Business Review, 2024)
The high intensity of private vehicle usage has led to uncontrolled road congestion. To encourage residents to switch to public transportation, the Surabaya City Government introduced Trans Semanggi Suroboyo. Trans Semanggi Suroboyo experienced a decrease in passengers in 2023, with a decline of 324,711 passengers. Based on a preliminary survey with direct interviews conducted with 35 Trans Semanggi Suroboyo passengers, frequent complaints were related to service and facilities. Therefore, it is important to analyze and propose improvements to the services of Trans Semanggi Suroboyo as public transportation in Surabaya. To enhance the quality of services and facilities, it is essential to identify and evaluate passenger perceptions using service quality dimensions based on the Decree of the Director General of Land Transportation Number SK.5923/AJ.005/DRJD/2016. The most important service quality priorities for passengers are measured using the Importance Performance Analysis (IPA) method. This research identified 9 critical attributes that require improvement. Subsequently, a service quality improvement design was developed using the Quality Function Deployment (QFD) approach through the House of Quality (HoQ) matrix, resulting in 5 priority technical responses. Based on these findings, a plan for improving the service and facilities of the Trans Semanggi Suroboyo bus was proposed to maintain the quality of public transportation services.